A conservative approach to a mesiodens removal via frenectomy incision. A case report - Daniel Guião-Fernandes; Kimberlly Avelar; Victoria Melo; Ana Clara Caetano; Lucas Padovani (Elsevier, 2022)
Hyperdontia is a condition when patient presents one or more supernumerary teeth in maxilla or mandible. When the supernumerary tooth is in the midline, above the upper incisors, it is called mesiodens. The aim of this paper is to report a case of a mesiodens extraction by means of a minimally invasive technique using an incision in the labial frenulum, avoiding releasing incisions and using platelet-rich fibrin (PRF) to fill the surgical site. A 13 year-old patient was referred to our clinic to extract a supernumerary tooth located above maxillary central incisor. After anesthesia and removal of the labial frenulum, a mucoperiosteal flap was raised bilaterally via tunneling. A careful osteotomy was performed and the tooth was cautiously removed with an apexo elevator. This technique provides a predictable and conservative approach and reduction in the procedure morbidity, also absence of scar in the anterior maxilla, not impacting aesthetics.